Candida Albicans 2019
DOI: 10.5772/intechopen.80683
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phagocytes in Immunity to Candida albicans

Abstract: Body clearance of fungi such as Candida albicans involves phagocytosis by fixed tissue macrophages as well as infiltrating monocytes and neutrophils. Through phagocytosis, the fungi are confined and killed by the oxidative and non-oxidative anti-microbial systems. These include oxygen derived reactive species, generated from the activation of the NADPH oxidase complex and granule constituents. These same mechanisms are responsible for the damage to hyphal forms of C. albicans. Complement promotes phagocytosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Even if no mechanistic assessment has been performed, we speculate that the two cytokines, TNF-α and IFN-γ, used in the tested MIM, respectively at 5 and 6 CH, could explain the enhanced phagocytic capacity of MIM-treated cells compared to vehicle-treated cells. It has been reported that phagocytosis and killing of C. albicans are enhanced by proinflammatory cytokines, in particular by TNF-α and IFN-γ [ 35 ]. The two cytokines may have worked synergistically, thus inducing autocrine positive feedbacks, as it was previously reported to happen with higher doses [ 20 , 21 ], finally boosting the phagocytic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Even if no mechanistic assessment has been performed, we speculate that the two cytokines, TNF-α and IFN-γ, used in the tested MIM, respectively at 5 and 6 CH, could explain the enhanced phagocytic capacity of MIM-treated cells compared to vehicle-treated cells. It has been reported that phagocytosis and killing of C. albicans are enhanced by proinflammatory cytokines, in particular by TNF-α and IFN-γ [ 35 ]. The two cytokines may have worked synergistically, thus inducing autocrine positive feedbacks, as it was previously reported to happen with higher doses [ 20 , 21 ], finally boosting the phagocytic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney cell cultures produced high levels of TNF-α and IL-10 but not IFN-γ, IL-17, and IL-2, suggesting that the cytokine cell source was predominantly from the innate immunity, probably phagocytes [ 51 , 52 ]. Phagocytes present in kidneys during Candida infections, including macrophages and neutrophils, are associated with fungal clearance and resolution of infection [ 53 ]. However, the renal inflammatory process may result in tissue damage and consequently affect the proper functioning of the organ [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data from the present study demonstrated that camel PBL generated a higher CL response with opsonized zymosan than with non-opsonized zymosan and interestingly, PBL from camels generated a significantly higher CL response in the absence of opsonins when compared to PBL from goats, sheep, and cows (unpublished observation). Small et al [43] observed that the CL response of peripheral blood mononuclear cells (PMN) was higher with opsonized zymosan than with non-opsonized zymosan. They attributed this primarily to ic3b, and to a lesser degree to C3b and IgG coated opsonized zymosan.…”
Section: Of Camel Pbl With Zymosan Opsonized With Heat-inactivated Serummentioning
confidence: 99%